Digital Transformation Now! Guiding the Successful Digitalization of Your Business Model - Schallmo, Daniel R. A. (SpringerBriefs in Business,, 2018)
Is digitalization a value-added approach? Global leaders believe so, and this book reveals how to digitally transform your business model and compete in today's economy. It presents a roadmap consisting of five phases; Digital Reality, Digital Ambition, Digital Potential, Digital Fit, and Digital Implementation, each with step-by-step instructions as well as innovative activities and tools. This is a timely book offering professionals a concise, tried-and-trusted guide to the digital transformation of business models.